Breast self examination: to do or not to do? - Leelavathi M,; Yasmin SAK,; Gomez PA,; Aznida FAA, (Penerbit UKM, 2006)
This is a retrospective descriptive study done to look at common presentation and method of detection of breast cancer. A total of 366 case records of patients attending the Breast and Endocrine Clinic at Hospital Kuala Lumpur were reviewed. The peak age of breast cancer presentation was 40 to 49 years (39.6%). Most (81.4%) patients presented with a lump in the breast and the lump was mainly self-detected (97.3%). The mean tumour diameter on presentation was 4.7± 3 cm. Medical staff detected the disease in 1.6% cases and 1.1% of cases were detected by mammogram. Most women detected the lump themselves, suggesting that Breast Self Examination (BSE) can be used for detection of the disease in places where there is cost and availability constrains for mammogram. Early detection with BSE can possibly offer better treatment options and quality of life despite the evidence that it does not reduce the mortality due to breast cancer.